STATUS GIZI DAN KEJADIAN ISPA PADA BALITA YANG BERKUNJUNG KE PUSKESMAS JALAN GEDANG KOTA BENGKULU - Nurul Khairani; Yusran Fauzi; Weldy Pratama H.S. (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
Acute respiratory infection (ARI) is the most important cause of morbidity and mortality in children. This study was conducted to study the relationship between nutritional status and the incidence of ARI of children under five who visited Jalan Gedang Public Health Center Bengkulu. This study aimed to determine the relationship between nutritional status with the incidence of ARI of children under five who visited Jalan Gedang Public Health Center Bengkulu. This research type was Analytical Survey and used Cross Sectional research design. This research was conducted in the working area of Jalan Gedang Public Health Center Bengkulu in July-August 2017. The population in this study were all mothers who had children under five aged 0-59 months who visited Jalan Gedang Public Health Center Bengkulu with using Accidental Sampling technique. Data collection in this research used primary data and secondary data. Data collection techniques used primary data by interview and observation based on questionnaires and secondary data was data obtained from register register form. Data analysis technique was done by using univariate and bivariate analysis with Chi-Square (χ2 ) test through SPSS program. To know closeness of relationship by using statistical test of Contingency Coefficient (C). The results of this study were from 104 children under five,, there were 85 children under five (81,7%) with good nutritional status and 67 children under five (64,4%) did not suffer from ARI, there was a significant relationship between nutritional status with the incidence of ARI in children under five who visited Jalan Gedang Public Health Center Bengkulu with close relationship categories. It was suggested to health workers to optimize the role in disseminating with the material about the relationship of nutritional status with the incidence of ARI in children under five..Keywords : ARI, children under five, nutritional status